Impact Analysis of Digital Divide on Food Security and Poverty in Indonesiain 2015-2017 - Yalina, Nita; Kartika, Akbar Pratama; Yudha, Ana Toni Roby Candra (SBM ITB, 2020)
Abstract. The purpose of this study is to analyze the impact of the digital divide on food security and poverty in Indonesia. The data were taken from the Indonesian Central Bureau of Statistics (Badan Pusat Statistik) from 2015 to 2017. This research used a quantitative method using Structural Equation Model (SEM). Digital divide, Food security and Poverty were the latent variables that were used in this research. The result of this study shows that the digital divide had a significant positive impact on food security while the impact of food security on poverty was negatively significant with the coefficient 0.894 and -0.616 respectively. There was no significant impact of the digital divide on poverty directly. It means that technology doesn't have any significant contribution to Poverty reduction in Indonesia. However, when the reduction from the data was conducted, and only specific province who have good ICT development were used, the result was different. ICT development had a significant impact to reduce poverty in Indonesia.Keywords: Digital divide, poverty, food security, SEM, Indonesia.Abstrak. Penelitian ini bertujuan untuk melakukan analisis pengaruh kesenjangan teknologi terhadap ketahanan pangan dan poverty di Indonesia. Data yang digunakan untuk keperluan analisis adalah data sekunder yang didapatkan dari Badan Pusat Statistik (BPS) sejak tahun 2015 hingga tahun 2017. Penelitian ini menggunakan pendekatan kuantitatif dengan menggunakan metode Structural Equation Model (SEM). Variabel laten yang digunakan untuk analisis ini adalah Kemajuan Teknologi, Kemiskinan, dan Ketahanan Pangan. Berdasarkan hasil penelitian, Kemajuan Teknologi berpengaruh secara positif dan signifikan terhadap Ketahanan Pangan dengan nilai koefisien 0.894, sementara ketahanan pangan berpengaruh negatif dan signifikan terhadap nilai kemiskinan dengan nilai koefisien sebesar -0.616. Tidak ada pengaruh signifikan antara variabel kemajuan teknologi terhadap kemiskinan secara langsung. Hal ini berarti bahwa kontribusi teknologi masih belum berpengaruh secara signifikan terhadap pengentasan kemiskinan di Indonesia.Kata kunci: Kesenjangan teknologi, kemiskinan, ketahanan pangan, SEM, Indonesia